EFEKTIVITAS KEPATUHAN MINUM OBAT TERHADAP STATUS GIZI PADA PENDERITA TUBERKULOSIS PARU (TBC) DI UPT PUSKESMAS BATURETNO - Handono, Nugroho Priyo (Jurnal AKPER GSH, 2020)
Background: Pulmonary tuberculosis is an infectious disease that attacks the lung parenchyma, caused by Mycobacterium tuberculosis. This disease can also spread to other parts of the body, such as the meninges, kidneys, bones and lymph nodes (Irman Soemantri, 2009). The prevalence of TB is estimated at 169 cases per 100,000 population, the incidence of pulmonary TB is 122 cases per 100,000 population and the mortality rate is 13 cases per 100,000 population (WHO, 2013). The prevalence of pulmonary TB in Central Java is 321 per 100,000 population (Riskes report, 2018). The Tuberculosis Case Notification Rate (CNR) for all cases was 118 per 100,000 population. Meanwhile, Wonogiri Regency was ranked 25th with CNR Tuberculosis of 75.2 per 100,000 population (Central Java Health Profile, 2016).Purpose of writing: To determine the relationship between adherence to taking anti-tuberculosis drugs (OAT) with the nutritional status of patients with pulmonary tuberculosis at UPT Puskesmas Baturetno.Methods: The study design was observational with a cross sectional approach to 33 pulmonary tuberculosis patients who were undergoing outpatient care at the UPT Puskesmas Baturetno. Subjects were selected by purposive sampling. Drug adherence data were obtained from questionnaires filled out through interviews with patients. Food intake data were obtained through the Semi Quantitative Food Frequency Questioner and analyzed by Nutrisurvey. Nutritional status was assessed based on the Weight for Age Z Score (WAZ) referring to the WHO Antro 2005 reference standard. Bivariate analysis used SPSS 20 with the Chi Square statistical test.Results: Most of the subjects (57.6%) complied with the medication regimen. At the beginning of diagnosis, 18.2% of children were malnourished and decreased by 9.1% after treatment. There was no correlation between medication adherence and nutritional status (r = 0.218; p = 0.223). The relationship between medication adherence and nutritional status after being controlled by energy and protein intake did not show a significant relationship (r = 0.184; p = 0.322).Conclusion: There is no correlation between medication adherence and nutritional status of patients with pulmonary tuberculosis at Baturetno Public Health Center